Technical challenges and opportunities in realising a circular economy for waste photovoltaic modules. (August 2020) - Farrell, C.C.; Osman, A.I.; Doherty, R.; Saad, M.; Zhang, X.; Murphy, A.; Harrison, J.; Vennard, A.S.M.; Kumaravel, V.; Al-Muhtaseb, A.H.; Rooney, D.W.
Abstract: The global exponential increase in annual photovoltaic (PV) installations and the resultant levels of PV waste is an increasing concern. It is estimated by 2050 there will be between 60 and 78 million tonnes of PV waste in circulation. This review will investigate and establish the most efficient routes to recycle end-of-life modules. It will consider current design constraints, focusing on the maximum recovery of constituents from the module, reporting on some of the latest advancements in recycling methodology at both industrial and laboratory scale. Circular challenges, opportunities, models and arguments are presented for critical analysis of closed-loop recycling alongside alternative open-loop cascading options. Adopting circular economy principles will help offset environmental factors such as emissions associated with the manufacturing stages and increase recycling & recovery rates. First-generation crystalline silicon (c-Si) modules have had an 80–90% market share over the last 40 years and will constitute the majority of the impending PV waste stream. These PV modules are composed of several material types such as glass, metal, semiconductor and polymer layers in a strongly bound laminate. This design makes reusing and maintaining these modules difficult and limits potential recycling options. Here we provide guidance for understanding the c-Si PV module manufacturing process and how to best approach the challenge of recycling this vast and inevitable waste stream. In conclusion, pyrolysis offers the best potential for the optimum recovery of material and energy found in first-generation c-Si modules to help promote a truly circular economy within the well-established PV industry. Highlights: An assessment of mechanical, thermal and chemical PV recycling routes was made. EU legislative policy and drivers for PV waste was discussed. Circular opportunities for PV waste was presented via closed-loop cascades. Sustainable development goals in the PV industry was highlighted and assessed. Pyrolysis was determined to be the most promising route to PV module delamination.